Catalogue of Indian Alysiinae (Hymenoptera: Braconidae) - Singh, Longjam Roni Kumar; Chandra, Kailash; Gupta, Devanshu (Zootaxa, 2021)
This catalogue of the Indian Alysiinae (Hymenoptera: Braconidae) is based primarily on an extensive survey of published data. A total of 67 species of Alysiinae including 13 genera and 60 species in the tribe Alysiini and five genera and seven species in Dacnusini are reported from India. Taxonomic history with details of synonyms, along with type localities, type depositories, and distribution in different states of India and biogeographic zones are provided. Two new combinations are proposed: Dinotrema viructae (Fischer, 1993) comb. nov. and Dinotrema matherana (Fischer, 1993) comb. nov. and one species is considered as an unavailable name. The Himalaya Biogeographic Zone supports the maximum diversity (45 species), followed by the Gangetic Plains (12 species), North-East (4 species), Western Ghats (4 species), Deccan Peninsula (4 species) and Semi-Arid (3 species).